Emergency department utilization by patients with gynecologic cancer in the United States. Issue 4 (12th October 2020) - Albright, Benjamin B; Delgado, Mucio K; Latif, Nawar A; Giuntoli, Robert L; Ko, Emily M; Haggerty, Ashley F
Abstract : Introduction: Payment reform will give oncologists increasing responsibility for how patients with cancer meet unexpected care needs. Objective: To differentiate how patients with gynecologic cancers use emergency care, and to assess the characteristics associated with potentially avoidable treat-and-release visits. Methods: We performed a retrospective cohort study using the Nationwide Emergency Department Sample, a stratified sample of visits in United States hospital-based emergency departments, from 2010 to 2014. Visits by patients with a diagnosis of gynecologic cancer were selected. Sample weights were applied to calculate national estimates of care patterns and trends. Associations with treat-and-release disposition were assessed with weighted logistic regression. Results: In the study period, patients with gynecologic cancer made an estimated 370 104 annual emergency department visits (95% CI 351 997 to 388 211). A total of 50.2% of patients were treated and released, 48% were admitted, 1.6% were transferred, and 0.1% died. These visits corresponded to over US1.27 billion in annual charges, with an average charge of US3428 per visit (95% CI 3348 to 3509). Driven by growing treat-and-release utilization, annual visits increased, while admission rates fell over time. Patients with cervical cancer represented the plurality (36%) of visits; they were relatively younger, of lower socioeconomic status, and had fewer co-morbidities. Models for treat-and-release disposition did not vary significantly across different cancer populations. In the all-cancer model, increased odds of treat-and-release disposition was associated with cervical cancer diagnosis, younger age, lesser Elixhauser co-morbidity, Medicare coverage (OR=1.19; p<0.001), Medicaid coverage (OR=1.25; p<0.001), uninsured status (OR=1.70; p<0.001), and weekend visits. Visits in the northeast, at urban hospitals, and in winter months showed decreased odds of treat-and-release disposition. Discussion: Patients with gynecologic cancers have been using the emergency department at increasing rates, primarily driven by treat-and-release visits that did not result in admission or death. Patients with cervical cancer have higher rates of treat-and-release utilization and may over-use emergency department care.